Photo‐electrochemical activity and selectivity of nanocrystalline BaTiO3 electrodes in water oxidation. Issue 2 (14th October 2020) - Klusáčková, Monika; Nebel, Roman; Krtil, Petr; Krýsová, Hana; Pittkowski, Rebecca K.; Macounová, Kateřina Minhová
Abstract: Nanocrystalline BaTiO3 photocatalysts were prepared by spray‐freeze/freeze‐drying procedure in presence of structure directing gelatin. The synthetic approach yields materials with particle sizes ranging between 20 and 60 nm conforming to cubic perovskite structure. Regardless of the structural differences, the materials show particle size independent bandgap energy of ca. 3.27 eV. All prepared materials are photo‐electrochemically active in water oxidation with intrinsic activity decreasing with decreasing particle size. The photo‐electrochemical activity of BaTiO3 in water oxidation is pH dependent with the hole charge transfer processes being significantly suppressed in alkaline media. Such a behavior can be ascribed to deprotonation of surface OH groups encountered in alkaline media that promotes surface state catalyzed electron transfer reactions at the illuminated BaTiO3 surface. The barium titanate shows the ability to oxidize water with formation of oxygen and ozone. The ozone formation is pronounced on large nanocrystals particularly in acid media. No ozone formation was observed in alkaline solutions.